A Study of Methods Used to Reduce Surgical Site Infections - Stuart R. Walker; Tara Anderson (Archives of Clinical and Experimental Surgery, 2012)
Objective: Surgical site infections (SSI) remain a cause for concern. The aim of this audit was to assess current practise in an Australian Teaching Hospital when compared to guidelines issued by NICE (UK). Methods: A prospective audit of cases passing through the operating theater complex of a teaching hospital over four weeks. Practise was assessed against criteria designed to reduce the incidence of SSI. Results: 570 surgical cases were analyzed. In 126 cases (22%), hair was removed pre-operatively, 84% via clippers and 15% via razor. There was a large variation in the type of skin preparation used, with aqueous betadine/iodine being the most common (377 cases). In 340 cases (61%), the skin preparation was allowed to dry prior to skin incision. In 161 cases, an occlusive drape was used (28%). 339 patients (59%) received prophylactic antibiotics. The appropriateness of antibiotic prophylaxis was reviewed in relation to local guidelines. In the 238 cases where the timing of the antibiotics was recorded, the mean time prior to incision was 18 mins (the range was 180 minutes to 15 minutes after the incision). 248 patients had no active warming in theater. Their mean temperature on arrival in recovery was 36.6 and deg;C. 292 patients had active warming. Their mean body temperature on arrival in recovery was 36.7 and deg;C (Student T test p = 0.222, 95% confidence interval -0.137 to 0.032). Conclusion: In this hospital there was poor compliance when measured against the NICE recommendations. [Arch Clin Exp Surg 2012; 1(1.000): 27-33]